Compounds enhancing human sperm motility identified using a high-throughput phenotypic screening platform. Issue 3 (20th January 2022) - Gruber, Franz S; Johnston, Zoe C; Norcross, Neil R; Georgiou, Irene; Wilson, Caroline; Read, Kevin D; Gilbert, Ian H; Swedlow, Jason R; Martins da Silva, Sarah; Barratt, Christopher L R
Abstract: STUDY QUESTION: Can a high-throughput screening (HTS) platform facilitate male fertility drug discovery? SUMMARY ANSWER: An HTS platform identified a large number of compounds that enhanced sperm motility. WHAT IS KNOWN ALREADY: Several efforts to find small molecules modulating sperm function have been performed but none have used high-throughput technology. STUDY DESIGN, SIZE, DURATION: Healthy donor semen samples were used and samples were pooled (3–5 donors per pool). Primary screening was performed singly; dose–response screening was performed in duplicate (using independent donor pools). PARTICIPANTS/MATERIALS, SETTING, METHODS: Spermatozoa isolated from healthy donors were prepared by density gradient centrifugation and incubated in 384-well plates with compounds (6.25 μM) to identify those compounds with enhancing effects on motility. Approximately 17 000 compounds from the libraries, ReFRAME, Prestwick, Tocris, LOPAC, CLOUD and MMV Pathogen Box, were screened. Dose–response experiments of screening hits were performed to confirm the enhancing effect on sperm motility. Experiments were performed in a university setting. MAIN RESULTS AND THE ROLE OF CHANCE: From our primary single concentration screening, 105 compounds elicited an enhancing effect on sperm motility compared to dimethylsulphoxide-treated wells. Confirmed enhancing compounds were grouped based on their annotated targets/target classes. A major target class, phosphodiesterase inhibitors, were identified, in particular PDE10A inhibitors as well as number of compounds not previously known to enhance human sperm motility, such as those related to GABA signalling. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Although this approach provides data about the activity of the compound, it is only a starting point. For example, further substantive experiments are necessary to provide a more comprehensive picture of each compound's activity, the effect on the kinetics of the cell populations and subpopulations, and their potential mechanisms of action. Compounds have been tested with prepared donor spermatozoa, incubated under non-capacitating conditions, and only incubated with compounds for a relatively short period of time. Therefore, the effect of compounds under different conditions, for example in whole semen, for longer incubation times, or using samples from patient groups, may be different and require further study. All experiments were performed in vitro . WIDER IMPLICATIONS OF THE FINDINGS: This phenotypic screening assay identified a large number of compounds that increased sperm motility. In addition to furthering our understanding of human sperm function, for example identifying new avenues for discovery, we highlight potential compounds as promising start-point for a medicinal chemistry programme for potential enhancement of male fertility. Moreover, with disclosure of the results of screening, we present a substantial resource to inform further work in the field. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the Bill and Melinda Gates Foundation, Scottish Funding Council and Scottish Universities Life Science Alliance. C.L.R.B. is Editor for RBMO. C.L.R.B. receives funding from Chief Scientists Office (Scotland), ESHRE and Genus PLC, consulting fees from Exscientia and lecture fees from Cooper Surgical and Ferring. S.M.d.S. is an Associate Editor of Human Reproduction, and an Associate Editor of Reproduction and Fertility . S.M.d.S. receives funding from Cooper Surgical and British Dietetic Society. No other authors declared a COI.